The Role of Public Relations in Managing the State-Owned Enterprise Reputation Crisis: A Conceptual Study of the Case of PT Pertamina (Persero) - Putri, Cindy Varelia; Anggraeny, Monicca; Chasanah, Siti Nur; Subrata, Pramudya Ibnu (Jurnal Genesis Indonesia, 2026)
This study examines the conceptual role of Public Relations (PR) in managing organizational reputation and public trust, with a particular focus on State-Owned Enterprises (SOEs) in the digital era. Rapid developments in information technology have increased the risk of reputational crises, requiring organizations to adopt transparent and responsive communication strategies. Using a conceptual paper approach and a structured literature review, this research synthesizes various theoretical frameworks, including Situational Crisis Communication Theory and the organization-public relationship model. The analysis indicates that PR functions as a strategic managerial pillar that builds "reputational capital" through consistent two-way communication, which acts as a buffer during organizational crises. Furthermore, the study explores how effective crisis communication strategies can mitigate public uncertainty and restore trust by maintaining social legitimacy. The resulting conceptual model provides a systematic framework for understanding the interplay between PR strategies, crisis management, and long-term reputation preservation. This research contributes to the theoretical expansion of organizational communication by addressing the research gap in the SOE context. It concludes that a proactive PR approach is essential for navigating the complex digital landscape and suggests that future empirical studies should validate this framework across diverse industrial sectors.